Community Service Activities (CSA): Increasing the Competitiveness of Furniture SMEs Through Digital Marketing Strategies: Community Service Activities (CSA): Increasing the Competitiveness of Furniture SMEs Through Digital Marketing Strategies - Putri, Erni Puspanantasari (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
Small and medium enterprises (SMEs) UD Meubel Maju Barokah is a small and medium enterprise engaged in the production of wooden furniture, such as doors, cabinets, frames, and other household furniture. This business has good product quality but has not been able to maximize digital marketing strategies in expanding market reach and increasing competitiveness. This community service activity aims to assist SMEs in implementing digital-based marketing strategies to increase product visibility and attract wider consumer interest. The method of implementing the activity is carried out through a participatory approach, starting from field observation and direct interviews with business actors to solution design and training and implementation assistance. The focus of the activity is directed at five main aspects, namely the use of social media (Instagram, Facebook, TikTok), periodic content creation, marketing through e-commerce (Tokopedia, Shopee), product catalog website development, and optimization of customer testimonials. The results of the community service activity are expected to enable SMEs to actively utilize digital media to promote products, communicate with consumers, and build a professional image. This strategy can increase customer interaction and expand market reach. Thus, this community service provides a real contribution in supporting the digitalization of local SME marketing so that they can survive and develop in the era of digital competition.